Examining the Role of Food Form on Children's Self-Regulation of Energy Intake - Reigh, Nicole A.; Rolls, Barbara J.; Francis, Lori A.; Buss, Kristin A.; Hayes, John E.; Hetherington, Marion M.; Moding, Kameron J.; Kling, Samantha M. R.; Keller, Kathleen L. (Frontiers in Nutrition, 2022)
Increasing childhood obesity rates in both the United States and worldwide demonstrate a need for better prevention and intervention strategies. However, little is understood about what factors influence children’s ability to sense and respond to hunger and fullness cues, a critical component of self-regulation of energy intake and maintenance of a healthy body weight. Research in adults suggests that food form may influence self-regulation of energy intake. More specifically, beverages are not as satiating as solid foods when matched for factors such as energy content, energy density, and volume and therefore elicit poorer energy intake self-regulation. However, much less is known about the impact of food form on children’s ability to regulate their energy intake. This report describes a study that will examine the relationship between biological, cognitive, and psychological factors and children’s appetite self-regulation (ASR). In this pre-registered report, we will examine the influence of food form on children’s short-term energy compensation, a proxy indicator of energy intake self-regulation. The study will employ a within-subjects, crossover design in which children (n=78) ages 4.5-6 years will attend five laboratory visits, each approximately 1 week apart. During each visit, children will be presented with one of five possible preload conditions, matched for weight, energy content and energy density: apple slices, apple sauce, apple juice, apple juice sweetened with non-nutritive sweetener (NNS), or no preload. The order of preload conditions will be pseudorandomized and counterbalanced across participants. Following consumption of the preload (or no preload), children will consume a standardized ad libitum test meal of common foods for this age group. We hypothesize that children will demonstrate poorer short-term energy compensation (greater meal intake) in response to the liquid and semi-solid preloads compared to the solid preload. Understanding how energy in various forms affects children’s ability to self-regulate intake has implications for dietary recommendations and will help identify those who are most at-risk for poor intake regulation and the development of obesity.